WISATA HALAL TREND BARU INDUSTRI PARIWISATA KOREA SELATAN - May Firdaw Arifiyatti (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Nowadays. The development and improvement of the tourism industry was initiated because of the large market demand so as to create a strong competitiveness in the international world. This is not far from the international tourism industry which is increasingly competitive with a basis in understanding the interests and needs of the community. Furthermore, many non-Muslim countries have sparked halal tourism. This paper was written to examine and assess the development of the tourism industry based on Halal Travel in South Korea, which became an industrial rival in the international world. The data in this article was obtained from a literature review from scientific journals, published manuscripts, the official website of the organization, and news articles in accordance with the study to be made. A tourism industry must pay attention to several aspects of a Muslim's halal lifestyle. Namely food in halal restaurants, halal accommodation which includes halal hotels or resorts. In addition, transportation is halal. Halal facilities with places of worship or prayer rooms in every hotel, airport or other public places. So with this, of course opening a window to be better, namely with the Government a lot of cooperation with Muslim nationalities to launch the development of halal travel.